IMPLEMENTATION OF THE EQUALITY EDUCATION PROGRAM THROUGH COLLABORATION OF PKBM CENTELLA ASIATICA AND RUMAH BELAJAR AN-NAJMA IN BENGKULU CITY - Mauly Anitiya; Harfiah Fadillah Rahmi; Yezi Fitria Maharani; Sela Munica; Melita Susanti (Universitas Negeri Medan, 2026)
This study examines the implementation of an equality education program through the collaboration between PKBM Centella Asiatica and Rumah Belajar An Najma in Bengkulu City. The study aims to analyze the implementation process, identify the forms of institutional collaboration, and explore factors influencing program effectiveness. A qualitative descriptive approach was employed, with data collected through observations, semi-structured interviews, and documentation involving PKBM managers, tutors, learning center administrators, and learners in Package B and Package C programs. Data were analyzed using the Miles and Huberman interactive model. The findings reveal that the collaboration has successfully expanded educational access for school dropouts and adult learners through a flexible, community-based learning system. The program integrates academic instruction, life skills, and religious values, creating a holistic learning environment that enhances learner motivation and participation. A clear division of responsibilities between the two institutions strengthens program implementation, while community support contributes to its sustainability. However, challenges remain, including limited facilities, inadequate digital infrastructure, and irregular learner attendance.